Prinsip - Prinsip Dasar Keluarga Dalam Membentuk Karakter Anak - Muhammad Yasin; Nor Habibah (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
The main character's education is carried out in the family. Because the family is a role model for children to be able to develop their potential and build their character, the role of the family is very important to shape the child's character to be good or bad. The author describes the role of the family in shaping the character of children, using descriptive analysis so as to know the principles of education in the family. The conclusion of this research is that the process of building character in the family can be done in various ways, one of which is through habituation, giving good examples, advice, punishment and motivating children. The achievement of the character education process in the family can be maximized if the children, parents and the environment are mutually sustainable.